2010
DOI: 10.1590/s0100-29452010005000076
|View full text |Cite
|
Sign up to set email alerts
|

Reação de laranjeiras-doces quanto à resistência a Guignardia citricarpa

Abstract: O objetivo deste trabalho foi determinar o comportamento de variedades de laranjas-doces quanto à resistência a Guignardia citricarpa, agente causal da mancha preta dos citros (MPC). Os ensaios foram conduzidos em dois campos, nos municípios de Rincão e Tambaú, SP. As mudas foram formadas em viveiro localizado na Estação Experimental de Citricultura de Bebedouro-SP. Para tal, foram utilizadas borbulhas de plantas cítricas existentes no Banco Ativo de Germoplasma de Citros da Estação Experimental de Citricultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
0
8
0
2
Order By: Relevance
“…Studies conducted in Brazil and Ghana under non-limiting inoculum and weather conditions for infection indicated a susceptibility period of six and seven months after fruit set, respectively Baldassari et al, 2006;Brentu et al, 2012), but longer periods were not evaluated. Cultivar field trials conducted in Brazil as well as studies comparing the rate of disease progress have indicated that cultivar reaction to the disease is more linked to the interaction of environmental factors with the dynamics of fruit maturation (Spósito et al, 2004;Sousa and de Goes, 2010), than cultivar resistance. Sweet orange fruits infected by P. citricarpa when they are 3 cm in diameter needed about eight months to develop symptoms.…”
Section: Fungicide Type Number Of Plotsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted in Brazil and Ghana under non-limiting inoculum and weather conditions for infection indicated a susceptibility period of six and seven months after fruit set, respectively Baldassari et al, 2006;Brentu et al, 2012), but longer periods were not evaluated. Cultivar field trials conducted in Brazil as well as studies comparing the rate of disease progress have indicated that cultivar reaction to the disease is more linked to the interaction of environmental factors with the dynamics of fruit maturation (Spósito et al, 2004;Sousa and de Goes, 2010), than cultivar resistance. Sweet orange fruits infected by P. citricarpa when they are 3 cm in diameter needed about eight months to develop symptoms.…”
Section: Fungicide Type Number Of Plotsmentioning
confidence: 99%
“…The association of the pathogen with the citrus pathway varies with the citrus species: lemons and latematuring sweet orange cultivars are generally considered to be more susceptible , mostly because they hang on the tree for a longer period and are therefore more exposed to pathogen inoculum during periods when environmental factors are suitable for disease development and have more time for symptom development. Early-maturing sweet orange cultivars are considered less susceptible as they are harvested earlier (Timmer, 1999;Spósito et al, 2004;Sousa and de Goes, 2010). Results from the meta-analysis (section 3.6.1) indicate that, under field trial conditions, disease incidences when using the best fungicide programmes ranged from 0.6 % to 7 % of CBS-affected fruit and from 7 % to 32 % with the least effective fungicides.…”
Section: Probability Of Association With the Pathway At Originmentioning
confidence: 99%
See 1 more Smart Citation
“…Part of this vulnerability to biotic agents is due to perennity of plants, lack of spatial and temporal discontinuity, and the existence of environments favorable to these agents for long period throughout the year (SOUSA ; GOES, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A relação ºBrix/acidez (BA) de 13,17 e de 12,11 nos frutos com a coloração da casca predominantemente amarela (EM2), e totalmente alaranjada (EM3), respectivamente, salienta uma maturação quase completa, e evidencia a característica ácida dos frutos nesses estádios de maturação, pois quanto mais baixa a relação, mais ácido é o produto, e vice-versa. Segundo Ting (1983) citado por Sousa (2009), apesar da relação sólidos solúveis/acidez somente descrever o sabor da fruta, é o melhor índice de maturação disponível, pois é de fácil determinação e se aproxima do grau de maturação real. Kays (1997), salienta que a relação BA, dá a percepção de doçura da fruta, e é geralmente desejável uma proporção igual ou superior a 20.…”
Section: Resultsunclassified